Analysis of key factors in prison violence reduction using VIKOR and Neutrosophic sets - Merly Claribel Morán Giler; Gaspar Santos Manaces Esaud; Ingrid Joselyne Díaz Basurto (Journal of Fuzzy Extension and Applications)
This article presents an innovative approach to analyzing the determinants and primary factors of prison violence, aiming to reduce its frequency. Neutrosophic sets are employed to address the complexity and uncertainty inherent in this phenomenon. The analysis centers on identifying key variables that influence the occurrence and intensity of violence in penitentiary settings and on developing effective strategies for its prevention and mitigation. Through the VIKOR method, relationships among variables such as overcrowding, intergroup rivalry, and the availability of resources and rehabilitation programs are examined. Additionally, Bipolar Neutrosophic Numbers (BNN) are applied to handle the uncertainty of data related to prison violence, accounting for diverse perceptions and opinions within the inmate population. This integrated methodology offers a comprehensive perspective on prison violence, facilitating the identification of preventive strategies and informed decision-making to promote safer and more peaceful penitentiary environments.